2011
DOI: 10.2166/wst.2011.693
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and seasonal variations and ecotoxicological significance of sediment trace metal concentrations in Kebir-Rhumel basin (Northeast of Algeria)

Abstract: This study sought to assess sediment contamination by trace metals (cadmium, chromium, cobalt, copper, manganese, nickel, lead and zinc), to localize contaminated sites and to identify environmental risk for aquatic organisms in Wadis of Kebir Rhumel basin in the Northeast of Algeria. Water and surficial sediments (0-5 cm) were sampled in winter, spring, summer and autumn from 37 sites along permanent Wadis of the Kebir Rhumel basin. Sediment trace metal contents were measured by Flame Atomic Absorption Spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 4 publications
(6 reference statements)
0
10
0
Order By: Relevance
“…The PEC sed was calculated to be 21.2 mg/kg wet weight, which substantially exceeds the threshold for Phase I assessment (10 μg/kg). However, manganese concentrations in top sediment in marine and estuarine environments vary widely from 10 to at least 4,000 mg/kg, which in all cases by far exceeds that maximally emitted from aquaculture (Sadiq and Zaidi, 1985;Cahill and Unger, 1993;Galasso et al, 2000;Sahli et al, 2011). For land-based aquaculture operations, such as ponds and raceways, the surface water downstream of the fish farm is considered the most sensitive compartment (EFSA, 2008b).…”
Section: Environmental Safety From Use In Aquaculture Feedsmentioning
confidence: 99%
“…The PEC sed was calculated to be 21.2 mg/kg wet weight, which substantially exceeds the threshold for Phase I assessment (10 μg/kg). However, manganese concentrations in top sediment in marine and estuarine environments vary widely from 10 to at least 4,000 mg/kg, which in all cases by far exceeds that maximally emitted from aquaculture (Sadiq and Zaidi, 1985;Cahill and Unger, 1993;Galasso et al, 2000;Sahli et al, 2011). For land-based aquaculture operations, such as ponds and raceways, the surface water downstream of the fish farm is considered the most sensitive compartment (EFSA, 2008b).…”
Section: Environmental Safety From Use In Aquaculture Feedsmentioning
confidence: 99%
“…Indeed, Sahli et al (2011) recorded similar values in sediments from unaffected sites of Rhumel Wadi.…”
Section: Metal Contentsmentioning
confidence: 52%
“…This increase is probably mainly induced by intensive vehicle traffic and emissions of some industrial complexes related to urban and A c c e p t e d M a n u s c r i p t 5 industrial areas in the Rhumel subbasin. Sahli et al (2011) reported that the sediment quality of Rhumel Wadi in this part is medium to poor for the studied metals (Sahli et al 2012).…”
Section: Metal Contentsmentioning
confidence: 80%
See 1 more Smart Citation
“…However, manganese concentrations in top sediment in marine and estuarine environments vary widely from 10 to at least 4000 mg/kg, which in all cases far exceeds that maximally emitted from aquaculture (Sadiq and Zaidi, 1985;Cahill and Unger, 1993;Galasso et al, 2000;Sahli et al, 2011). When fed to fish in seacages, the sediment under the cage is considered the compartment of concern (EFSA, 2008b).…”
Section: Environmental Safety From Use In Aquaculture Feedsmentioning
confidence: 99%